Nystagmus at the Onset of Vertiginous Attack in Ménière's Disease. Issue 1 (January 2017) - Hirai, Chiaki; Yamamoto, Yukiko; Takeda, Takamori; Tasaki, Akihisa; Inaba, Yuichiro; Kiyokawa, Yusuke; Suzuki, Yasuhiro; Tsutsumi, Takeshi
Abstract : Objective: To clarify the direction and characteristics of nystagmus at the onset of a vertiginous attack in Ménière's disease. Patients: Two patients with Ménière's disease, whose nystagmus at the onset of a vertiginous attack was recorded using electronystagmography. Interventions: Diagnostic. Main Outcome Measures: Electronystagmographic recordings of nystagmus. Results: In both patients, nystagmus was directed toward the affected side over the entire course of the vertiginous attack. One patient experienced a severe sensation of vertigo and exhibited strong nystagmus from the onset of the attack. The other patient reported a mild sensation of vertigo, which was accompanied by intermittent nystagmus. Conclusions: Vertiginous attacks in Ménière's disease are accompanied by irritative nystagmus. The intensity and characteristics (e.g., continuous or intermittent expression) of the nystagmus may be associated with pathophysiological severity.